Biochar: Pemanfaatan dan Aplikasi Praktis - Rusdi Evizal; Fembriarti Erry Prasmatiwi (JURNAL AGROTROPIKA, 2023)
Biochar is a carbon-rich solid produced from the pyrolysis of biomass such as wood, manure, and leaves under high temperature and low oxygen conditions which is used for agricultural applications as a soil amendment. This paper reviews the utilization and practical application of biochar. The application of biochar into the soil can improve the physical, chemical and biological properties of the soil, namely increasing porosity, water holding capacity, soil aggregation, increasing pH, cation exchange capacity, soil organic carbon, nutrient retention and availability, and increasing microbial life, meso and soil macrofauna. Aside from being a soil amendment, biochar has a function on issues of global warming, climate change, and the environment, namely its role in carbon sequestration and stabilization, greenhouse gas emissions, and soil pollutant remediation. If biochar is applied properly, namely using the right feedstock materials, method of manufacture, dosage, method of application, and place, it will affect agronomic performance and crop yields. Reduced yields are mostly occured in temperate climates as biochar significantly increases soil pH causing an effect of excessive liming resulting in immobilization of key nutrients such as Mg, Fe, B, and P. Biochar needs to be mixed or applied together with fertilizer ingredients such as chemical fertilizers, bio-fertilizers, compost, and manure. Another effort is to enrich biochar with those materials so that biochar is categorized as a biochar-based fertilizer that has a higher selling price. Key words : Application, biochar, benefit, method, crop yield